Optimization of Purple Sweet Potato as a Partial Substitute for White Glutinous Rice in the Production of Solid Brem - Sucipto, Sucipto; Mandasari, Restu Ari; Issa, Zuraini Mat; Pulungan, Maimunah Hindun (Department of Agro-industrial Technology, University of Brawijaya, 2025)
AbstractSolid brem is a traditional Indonesian fermented product derived from white glutinous rice, whose increasing cost and demand necessitate the exploration of alternative raw materials. This study investigates the potential of purple sweet potato as a partial substitute for white glutinous rice in the production of solid brem and optimizes processing conditions to achieve desirable product quality. Response Surface Methodology (RSM) with a two-factor design was used to evaluate the effects of tape filtrate proportion (purple sweet potato to white glutinous rice, 0.5–1.5 v/v) and stirring time (15–45 min) on texture, moisture content, and Total Soluble Solids (TSS). The optimal conditions were a tape filtrate proportion of 0.86 (v/v) and a stirring time of 43.25 min, yielding a texture of 151.8 N, a moisture content of 12.14%, and a TSS of 12.2 °Brix. Sensory evaluation demonstrated that the developed product was generally accepted by consumers, with mean hedonic scores of 6.10 for appearance, 5.75 for taste, and 5.40 for aroma (on a 7-point scale). These findings highlight the feasibility of using purple sweet potato as a cost-effective and functional substitute in solid brem production, with acceptable physicochemical and sensory properties. This study contributes to the diversification of local raw materials and supports the development of sustainable agroindustrial products.Keywords: glutinous rice, purple sweet potato, solid brem AbstrakBrem padat adalah produk fermentasi tradisional Indonesia dari beras ketan putih yang mengalami peningkatan biaya dan permintaannya, sehingga perlu eksplorasi bahan baku alternatif. Studi ini menyelidiki potensi ubi ungu sebagai pengganti sebagian beras ketan putih dalam produksi brem padat dan mengoptimalkan kondisi pengolahan untuk mencapai kualitas produk yang diinginkan. Metode Response Surface Methodology (RSM) dengan desain dua faktor digunakan untuk mengevaluasi pengaruh proporsi air tape (ubi ungu terhadap beras ketan putih, 0,5–1,5 v/v) dan waktu pengadukan (15–45 menit) terhadap tekstur, kadar air, dan Total Solube Solids (TSS). Hasil optimasi menunjukkan bahwa kondisi optimal adalah proporsi air tape 0,86 (v/v) dan waktu pengadukan 43,25 menit, menghasilkan tekstur 151,8 N, kadar air 12,14%, dan TSS 12,2 °Brix. Evaluasi sensorik menunjukkan bahwa produk yang dikembangkan secara umum diterima oleh konsumen, dengan skor hedonik rata-rata 6,10 untuk penampilan, 5,75 untuk rasa, dan 5,40 untuk aroma (pada skala 7 poin). Temuan ini menyoroti kelayakan penggunaan ubi ungu sebagai pengganti yang hemat biaya dan fungsional dalam produksi brem padat, dengan sifat fisikokimia dan sensorik yang dapat diterima. Studi ini berkontribusi pada diversifikasi bahan baku lokal dan mendukung pengembangan produk agroindustri berkelanjutan.Kata kunci: beras ketan, brem padat, ubi ungu